Comparison of Balance and Muscle Activity of Normal Male and Female in Squats Exercise According to Knee Joint Angle (Medico Legal Update, 2019)
The purpose of this study was to analysis the balance and muscle activity with squats exercise according tothe knee joint knee between male and female. Before experiment, MVIC values were measured, and balanceand muscle activity were measured during the squat exercise using MATLAB and EMG. Shapiro-Wilk testwas used for normality test and Independent T test was used for independence test. All statistical significancelevels were p.05), but 90°showed significant difference (p